Study on numerical calculation method for hydrodynamic parameters of WEC - Lijiao Shen (MATEC Web of Conferences, 2017)
For the effect of hydrodynamic parameters on the dynamic performance of wave energy devices is very significant, these parameters must be considered carefully when adjusting dynamic characteristics of devices. On the other hand calculating hydrodynamic parameter of devices accurately can guarantee rational dynamic property parameter adjustment. By using CFD technique and considering the definition of hydrodynamic parameters, the phase relationship between added mass and damp as well as the equation of forces, one new calculation method of hydrodynamic parameter was presented. Finally one example demonstrated the effectiveness of the new analysis method presented in this paper.